60*80=eh*fh

Simple and best practice solution for 60*80=eh*fh equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 60*80=eh*fh equation:


Simplifying
60 * 80 = eh * fh

Multiply 60 * 80
4800 = eh * fh

Multiply eh * fh
4800 = efh2

Solving
4800 = efh2

Solving for variable 'e'.

Move all terms containing e to the left, all other terms to the right.

Add '-1efh2' to each side of the equation.
4800 + -1efh2 = efh2 + -1efh2

Combine like terms: efh2 + -1efh2 = 0
4800 + -1efh2 = 0

Add '-4800' to each side of the equation.
4800 + -4800 + -1efh2 = 0 + -4800

Combine like terms: 4800 + -4800 = 0
0 + -1efh2 = 0 + -4800
-1efh2 = 0 + -4800

Combine like terms: 0 + -4800 = -4800
-1efh2 = -4800

Divide each side by '-1fh2'.
e = 4800f-1h-2

Simplifying
e = 4800f-1h-2

See similar equations:

| 60*80=4800 | | 60*80= | | 54*96=kl*kl | | -11-10=10y | | -4+n=12 | | b^4+4= | | 81x^3+3y^3= | | (4x+3)+(7x)+(3x)=180 | | (4x-3)+(7x)+(3x)=180 | | 14x-3=180 | | 7(x+8)=7(x-3) | | 9x=8-5x^2 | | b=88(1/4)+1 | | X^5+3X^3+7=0 | | y=(x-2)(x-1) | | 9a=a+8a | | 14z=z+13z | | 111=a+a(1/4)+1 | | z-6=3 | | 2x-4=15x+9 | | 3(0.9x-0.34)=6(0.3x-0.4) | | 27-3x-18= | | 0.76x+0.5=0.23x+0.45 | | 5*45=x*x | | 9*16=x*x | | 5*20=x*x | | 3*12=x*x | | 7*28=x*x | | 3*27=x*x | | -4x^2*(3x^2-x+1)= | | 2*8=x*x | | 68*20=z*17 |

Equations solver categories